A Comparison Of Power Flow Based On Bus Admittance Matrix For Networked Microgrid Energy Management - Mohd Yassim, Halyani; Abdullah, Mohd Noor; Kim Gan, Chin (2024)
A networked microgrid with an energy management system connects several microgrids to exchange power for cost-effective and reliable operation. The feasibility study is required as a basis for developing an efficient networked microgrid energy management plan. This paper presented a detailed power flow analysis of a networked microgrid. Multiple IEEE microgrids are interconnected in the networked microgrid system, and various types of distributed generators are modeled based on PQ and PV control schemes. Different power flow algorithms based on the bus admittance matrix are used in the MATLAB simulation. Several case studies demonstrated the feasibility of the networked microgrid in grid connected and islanded modes as well as the effectiveness of the Fast-Decoupled (BX version) method in facilitating power exchange between microgrids to maintain supply-demand balance under normal and abnormal conditions. The results proved that the Fast- Decoupled (BX version) method is significantly faster than the Fast- Decoupled (XB version) and Newton-Raphson methods and has better convergence than the Gauss-Seidel method.